Análise mecânica em elevadas temperaturas de barras poliméricas reforçadas com fibra de vidro - Trevisan, Rafael (Universidade do Vale do Rio dos Sinos, 2023)
One of the main damages in reinforced concrete structures is the corrosion of the steel reinforcements. As an alternative to this scenario, there is the use of polymer bars reinforced with glass fiber (GFRP – Glass Fiber reinforced Polymer), increasing durability. The material also has reduced mass compared to steel bars and also high tensile strength. In order to use these bars, it is necessary to study their behavior in the face of accidents such as fires and the action of high temperatures, objective of this study. Specifically, the study evaluated the elastic modulus and direct tensile strength of the bars during and after exposure to high temperatures. The experimental program characterized the bar at room temperature. Afterward, the bars were tested during and after exposure to temperatures at levels of 150, 200, 250, 300, and 350 ºC. After exposure to high temperatures, the bars were evaluated with scanning electron microscopy (SEM), and the resin consumption was evaluated through the fiber content test. The indicated results indicate that the fiber content was in accordance with the assumptions of the IBRACON/ABECE recommended practices and international standards. Regarding exposure at high temperatures, it was noticed that the damage was more severe in the tests carried out during the high temperatures than in the bars after this exposure. The reduction in direct tensile strength reached 37% at a temperature of 350 °C. The greatest reduction in the modulus of elasticity, however, was 8.3%, indicating that the performance of the fibers was not so compromised even in the face of exposure to heat. For tests after exposure to high temperatures, the greatest reduction in tensile strength occurred at 150 ºC, being less than 1%. For the modulus of elasticity in this condition, the greatest reduction was 7.9%, observed at 200 ºC. The glass transition temperature obtained was 101.75 ºC. Through scanning electron microscopy, it was possible to perceive flaws that result from the consumption of resin due to the action of heat, such as: surface damage, flaws, less thickness of fiber cover, fiber breakage, among others. The fiber content test after high temperatures showed a direct relationship with the reduction of mechanical properties.
Keywords: Elevadas temperaturas; Barras poliméricas; Propriedades mecânicas; High temperatures; Polymer bars; Mechanical properties; ACCNPQ::Engenharias::Engenharia Civil